Intention to Leave the Profession in Iranian Nurses: The Predictive Role of Organizational Commitment and Burnout - Amiri, Mohammad; Velzi, Diar; Mirhosseini, Seyedmohammad; Khosravi, Ahmad (Shahroud Journal of Medical Sciences, 2025)
Background: Organizational commitment and human resource retention have gained increasing attention in healthcare. This study examined the relationship between organizational commitment, burnout, and intention to leave the profession among Iranian nurses. Methods: In this analytical cross-sectional study, 118 nurses with at least one year of work experience from Shahroud, Iran, were selected via simple random sampling. Data were collected using validated questionnaires on organizational commitment, burnout, and intention to leave the profession. ANOVA and Chi-square tests were used for group comparisons, and multiple linear regression (by backward method) was conducted to assess predictors of intention to leave, with a significance level of 0.05. Results: The mean scores for organizational commitment, burnout, and intention to leave were 93.54±9.37, 62.86±17.26, and 43.49±10.47, respectively, indicating average levels among nurses. Organizational commitment, burnout, job interest, and work experience emerged as significant predictors of intention to leave. Each one-point increase in organizational commitment was associated with a 0.2-point decrease in the intention to leave. Moreover, nurses with 10–20 and over 20 years of experience showed a 2.5-point reduction in intention to leave compared to those with less experience. Conclusions: The average levels of organizational commitment, burnout, and intention to leave among nurses highlight the need for managerial interventions. Enhancing organizational support through strategies such as optimizing work schedules, revising salary systems, involving nurses in decision-making, improving workplace conditions, offering constructive feedback, and providing in-service training may strengthen organizational commitment, reduce burnout, and ultimately decrease nurses' intention to leave the profession.